2014
DOI: 10.1111/jcpp.12326
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of early callous‐unemotional, oppositional, and ADHD behaviors: multiple domains within early‐starting conduct problems?

Abstract: Background Early-starting child conduct problems (CP) are linked to the development of persistent antisocial behavior. Researchers have theorized multiple pathways to CP and that CP comprise separable domains, marked by callous unemotional (CU) behavior, oppositional behavior, or ADHD symptoms. However, a lack of empirical evidence exists from studies that have examined whether there are unique correlates of these domains. Methods We examined differential correlates of CU, oppositional, and ADHD behaviors du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
120
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 36 publications
18
120
1
2
Order By: Relevance
“…First, in response to the concern that CU traits may not be identifiable as separable from conduct problems, we showed using CFA that mothers' ratings of CU traits were separable from ratings of physical aggression at age 2.5 years. This builds on previous findings which have demonstrated that CU traits are distinct from other problem behaviour dimensions at age 3 years and above (Willoughby et al, 2011;Willoughby et al, 2013;Waller et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…First, in response to the concern that CU traits may not be identifiable as separable from conduct problems, we showed using CFA that mothers' ratings of CU traits were separable from ratings of physical aggression at age 2.5 years. This builds on previous findings which have demonstrated that CU traits are distinct from other problem behaviour dimensions at age 3 years and above (Willoughby et al, 2011;Willoughby et al, 2013;Waller et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Hyde et al (2013) found their age 3 deceitful-callous measure to predict increased behaviour problems from age 2 to 4 years after accounting for initial problem behaviour. Further, Waller et al (2015) found age 3 mother-reported CU traits predicted teacher-reported externalizing problems at age 6, after accounting for age 3 externalizing problems. No study has yet shown incremental validity for a CU trait measure in 2 year olds in this way.…”
Section: Validity Of Cu Traits Measures In Early Childhoodmentioning
confidence: 88%
See 2 more Smart Citations
“…Although direct prospective links from low ailiative behavior have not been tested, recent studies suggest that callous-unemotional behaviors are related to lower quality of positive afective parent-child interactions, including lower eye contact, warmth, [66,67] and empathy [68].…”
Section: Temperament and Personalitymentioning
confidence: 99%